Two New M23 Peptidoglycan Hydrolases With Distinct Net Charge - Wysocka, Alicja; Jagielska, Elżbieta; Łężniak, Łukasz; Sabała, Izabela (Frontiers in Microbiology, 2021)
Bacterial peptidoglycan (PG) hydrolases play an essential role in the cell wall metabolism during bacterial growth, division and elongation (autolysins) or in elimination of closely related species from the same ecological niche (bacteriocines). Most studies concerning the ones present in Gram-positive bacteria focus on clinically relevant Staphylococcus aureus or model organism Bacillus subtilis, but the knowledge concerning other species is limited. Here we report two new peptidoglycan hydrolases from M23 family of metallopeptidases, which derive from the same staphylococcal species, Staphylococcus pettenkoferi. They share modular architecture, significant sequence identity (60%), catalytic and binding residues conservation and similar mode of activation, but differ in gene distribution, putative biological role and what is the most striking, in their isoelectric points (pI). One of them has high pI, as almost all M23 peptidases reported so far, while the other display low pI, a very unique feature among M23 peptidases. Consequently, we named them M23_A (“Acidic”) and M23_B (“Basic”). Upon combining genetic and biochemical approaches we have characterised two novel lytic enzymes both in vitro and in their physiological context. Our study presents detailed characterisation of the novel and clearly distinct PG hydrolases in order to understand their role for the bacterial physiology.